Digital Khulʿ and Algorithmic Mediation in Indonesia’s e-Court: Redefining Female Agency in Islamic Family Law - Muhtar, Amin; Pujiono; Fatahillah, Wilnan; Sani, Tajudeen; Abdulghani, Naser Ali (Islamic Law and Social Issues in Society, 2026)
Indonesia’s e-Court, mandatory since Supreme Court Regulation (Perma) No. 7/2022, hosts the world’s largest digital khulʿ (wife-initiated divorce) infrastructure, yet how algorithmic mediation reshapes women’s agency under Islamic family law remains underexamined. Current research on khulʿ typically examines it from the perspectives of classical fiqh or procedural efficiency, neglecting women's legal consciousness and the design of the platform itself. This study asks how Indonesian women negotiate sharia agency within a digital system that classifies experience into algorithmic categories. It involves a qualitative case study based on semi-structured interviews with five Indonesian women who completed e-Court khulʿ filings (2022–2024), alongside an analysis of platform interfaces, Perma regulations, and the Muhammadiyah Tarjih Fatwa. The data are analyzed through post-structural feminism, legal consciousness theory, and algorithmic legalism, maqāṣid al-sharīʿah (the objectives of Islamic law). The findings highlight a concept of algorithmic-muʿāmalah (transactional Islamic law), where women’s agency is shaped by partial, contextual negotiations rather than full autonomy: they reinterpret algorithmic inputs into sharia-based justifications, use free-text fields to resist in a parodic way, and strategically time procedural steps. Mediation through the platform is neither entirely oppressive nor liberating. Outcomes stratify by digital literacy, access to female religious counsel (ʿālimāt), and post-filing economic exposure. The study contributes algorithmic-muʿāmalah as a new analytical category, repositions female agency from the courtroom to the platform interface, and proposes reforms rooted in maqāṣid: female muftī (Islamic jurist) oversight, context-detection for psychological harm (ḍarar nafsānī), legal cause (ʿillah), and platform-level research aligned with SDG 5 and SDG 16.